Efficacy and safety of mifepristone-misoprostol combination with extraamniotic ethacridine lactate-misoprostol for termination of second trimester pregnancy - G., Hemavathi; C., Jagruthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Mid trimester termination of pregnancy is one of the most controversial areas of gynecological practice. It has moral, emotional, social and technical issues. This study was designed for comparison of efficacy and safety of Mifepristone-Misoprostol combination with exrtaamniotic Ethacridine Lactate-misoprostol for termination of second trimester pregnancy. Methods: The present was undertaken among the patients admitted to hospitals attached to J.J.M. Medical College; Bapuji hospital, Women and Children hospital and Chigateri general hospital Davangere during the study period from November 2016 - October 2017. Patients coming for second trimester abortion to above mentioned hospitals were assigned serial number from 1 to 80 and all patients with even number will be allocated to group 1 and all patients with odd number will be allocated in group 2, each group comprising 40 women each. Results: Majority of the cases in both the groups were between 21-25 yrs. Majority of the cases in both the groups were multigravidas. 11 cases from group 1 and 12 cases from group 2 were of gestational age between 14-16 wks. 29 cases from group 1 and 28 cases from group 2 were of gestational age between 18-20 wks. In the present study the mean induction abortion interval for group 1 was 19.56±1.82 hours and group 2 was 14.13±2.72 hours. This was statistically significant. Of the 40 cases in each group, 37 had complete abortion i.e. 92.5% 3 cases (7.5%) from both the groups had incomplete abortion. The side effects were relatively more in more in group 1 when compared to group 2. Conclusions: It was concluded that with this combination success rate was high (92.5 %), with Short induction abortion interval, less rate of incomplete abortion without any major complications.